Analisa Putusan ICSID Atas Sengketa Churchill Mining Plc, Planet Mining Dengan Pemerintah Indonesia Berdasarkan Prinsip Unidroit - Lubis, Devi Triana (Fakultas Hukum Universitas Trisakti, 2022)
Disputes in international arbitration cases are decided by an international arbitral forum that has been agreed upon and appointed by the parties through the arbitral clause listed in the international investment contract which binds the parties. In the dispute cases ARB/12/14 and ARB-12/40 between Churchill Mining Plc, Planet Mining and the Government of Indonesia decided by ICSID as the forum choice. The purpose of this study is to describe and analyse the judgments in cases ARB/12/14 and ARB-12/40 to find out the correlation between such judgements and the principle of commercial contracts contained in UNIDROIT 2010 principles. The formula of the problem that the author discusses, is how the principles are compatible with the ICSID judgment on the case. Normative research methods, descriptive writing properties, type of data used are secondary data, data analysis is performed qualitatively, as well as conclusion-taking is done using deductive logic. Based on the results of the research, the author can conclude that the basis of the judgment has been in accordance with the 2010 UNIDROIT Principles.